PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENYULUHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA PERTANIAN (BPPSDMP) KEMENTERIAN PERTANIAN : Introduction, Literature Review, Methods, Results and Discussion, Discussion, Conclusion, Suggestions, Bibliography - Rizki, Mutiara; Nurhayaty, Ety (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2023)
Performance is the achievement of a job that has been done by employees both individually and in groups, and this in the assessment has been adjusted to the standards applicable in each agency. Every organization or agency certainly really wants good performance appraisal results for its employees. With the purpose of this study, it is used to determine the influence of the Work Environment on the performance of employees (BPPSDMP) of the Ministry of Agriculture, to determine the effect of Work Discipline on the performance of employees (BPPSDMP) of the Ministry of Agriculture. and to determine the effect of Work Environment and Work Discipline simultaneously on employee performance at the Human Resources Extension and Development Agency (BPPSDMP) of the Ministry of Agriculture. This research is a causal associative research with a quantitative approach. The sample of this study amounted to 71 employees. The sampling technique uses Simple Random Sampling Technique. Data collection techniques use primary and secondary data. The data analysis technique, namely Multiple Linear Regression, this study used the help of SPSS 25 Application. Based on the results of this study, it shows that there is a positive and significant influence between the work environment and work discipline on the performance of employees of the Human Resources Extension and Development Agency (BPPSDMP) of the Ministry of Agriculture with a correlation coefficient (R2) of 0.682, this is that 68% of employee performance in the Extension and Human Resources Development Agency (BPPSDMP) of the Ministry of Agriculture is influenced by the work environment and discipline work, while for the other 30.2% influenced by other variables that were not explained in this study